2019
DOI: 10.1037/cou0000339
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities between genderqueer, transgender, and cisgender individuals: An extension of minority stress theory.

Abstract: This study suggests that individuals who identify outside the gender binary (e.g., genderqueer, gender nonconforming) experience more discrimination, victimization, poor mental health outcomes, and suicidality or self-harm than do both trans-and cisgender men and women. It highlights sociocultural factors such as lack of knowledge about genderqueer experiences and pronouns, poor access to legal and medical resources, and systemic discrimination that may be responsible for these trends. 396A Caballo Regalao no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
3
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(238 citation statements)
references
References 45 publications
(118 reference statements)
15
199
3
7
Order By: Relevance
“…These findings are consistent with the USTS, which found that the prevalence of homelessness was substantially higher among respondents whose immediate family had kicked them out of the house, with nearly three-quarters (74%) of these respondents experiencing homelessness. [11] While family rejection was higher for non-binary participants in the present sample, contrary to what was anticipated, [19] no significant differences were found in the prevalence of childhood sexual abuse, bullying, lifetime physical and sexual assault, or relevant protective factors such as number of close friends. Indeed, nonbinary participants did report significantly lower lifetime experiences of IPV relative to binary participants, which could be explained in part by the finding that non-binary individuals were less likely to be sexually active, though no differences were found according to current relationship status.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…These findings are consistent with the USTS, which found that the prevalence of homelessness was substantially higher among respondents whose immediate family had kicked them out of the house, with nearly three-quarters (74%) of these respondents experiencing homelessness. [11] While family rejection was higher for non-binary participants in the present sample, contrary to what was anticipated, [19] no significant differences were found in the prevalence of childhood sexual abuse, bullying, lifetime physical and sexual assault, or relevant protective factors such as number of close friends. Indeed, nonbinary participants did report significantly lower lifetime experiences of IPV relative to binary participants, which could be explained in part by the finding that non-binary individuals were less likely to be sexually active, though no differences were found according to current relationship status.…”
Section: Discussioncontrasting
confidence: 82%
“…Some research has found higher prevalence of harassment, trauma, and sexual assault for non-binary young adults relative to those who identify as binary. [19] The USTS survey showed only slight differences in the prevalence of lifetime sexual assault by binary gender identity (44% binary vs. 46% non-binary); however, binary individuals were more likely to be physically attacked (29%) and sexually assaulted (15%) in grades kindergarten through 12 th grade, relative to non-binary individuals (16%). In a clinical sample of patients at an urban health center, past-12 month intimate partner violence (IPV) rates were elevated for transgender women (12.1%), transgender men (6.6%), and non-binary individuals (8.2%) relative to cisgender women (2.7%) (p<0.05).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some research suggests that individuals who have lower levels of educational attainment and lower levels of income may experience more discrimination (Bradford, Reisner, Honnald, & Xavier, ). In addition, recent findings show that genderqueer individuals experience greater harassment and other minority stressors compared to trans men and trans women (Lefevor, Boyd‐Rogers, Sprague, & Janis, ).…”
Section: Minority Stress Exposure For Tgd Individualsmentioning
confidence: 99%